# Solve this math problem!

## Recommended Posts

I need to see if we're wrong or the book is wrong. :D

I added the parentheses to keep the fractions straight, but it's exactly as written otherwise.

Oh, and show your work. ;)

2 - y + 10 + (y/2) = 3y - (7/3) + 2y

##### Share on other sites

2 - y + 10 + (y/2) = 3y - (7/3) + 2y

12 - (y/2) = 5y - (7/3)

12 + (7/3) = 5y + (y/2)

43/3 = (11/2)y

y = (43/3)/(11/2)

y = (43/3) * (2/11)

Y = 86/33

Y = 2 (20/33)

##### Share on other sites

Okay, where did your first y go? That's where we're lost.

##### Share on other sites

Never mind - it clicked!

##### Share on other sites

Left Hand Side

2 - y + 10 + (y/2) = 2 + 10 - y + (y/2)

= 12 - (y/2)

Right hand side

3y - (7/3) + 2y = 3y + 2y - (7/3)

= 5y - (7/3)

LHS = RHS

12 - (y/2) = 5y - (7/3)

ETA: saw that you solved it while I was typing :)

## Join the conversation

You can post now and register later. If you have an account, sign in now to post with your account.

×   Pasted as rich text.   Paste as plain text instead

Only 75 emoji are allowed.